Weak nonmesonic decay spectra of hypernuclei - Bauer, Eduardo; Galeao, Alfredo Pio Noronha Rodrigues [UNESP]; Hussein, Mahir S.; Krmpotic, Franjo (Elsevier B.V., 2010)
We compute one- and two-nucleon kinetic-energy spectra and opening-angle distributions for the nonmesonic weak decay of several hypernuclei, and compare our results with some recent data. The decay dynamics is described by transition potentials of the one-meson-exchange type, and the nuclear structure aspects by two versions of the independent-particle shell model (IPSM). In version IPSM-a, the bole states are treated as stationary, while in version IPSM-b the deep-hole ones are considered to be quasi-stationary and are described by Breit-Wigner distributions.